Study of New Thiazole Based Pyridine Derivatives as Potential Corrosion Inhibitors for Mild Steel: Theoretical and Experimental Approach. (3rd March 2016) - Chaitra, T. K.; Mohana, K. N.; Tandon, H. C.
Abstract : Three new thiazole based pyridine derivatives 5-(4-methoxy-phenyl)-thiazole-2-carboxylic acid pyridin-2-ylmethylene-hydrazide (2-MTPH), 5-(4-methoxy-phenyl)-thiazole-2-carboxylic acid pyridin-3-ylmethylene-hydrazide (3-MTPH), and 5-(4-methoxy-phenyl)-thiazole-2-carboxylic acid pyridin-4-ylmethylene-hydrazide (4-MTPH) were synthesized and characterized. Corrosion inhibition performance of the prepared compounds on mild steel in 0.5 M HCl was studied using gravimetric, potentiodynamic polarisation, and electrochemical impedance techniques. Inhibition efficiency has direct relation with concentration and inverse relation with temperature. Thermodynamic parameters for dissolution and adsorption process were evaluated. Polarisation study reveals that compounds act as both anodic and cathodic inhibitors with emphasis on the former. Impedance study shows that decrease in charge transfer resistance is responsible for effective protection of steel surface by inhibitors. The film formed on the mild steel was investigated using FTIR, SEM, and EDX spectroscopy. Quantum chemical parameters like E H O M O, E L U M O, Δ E, hardness, softness, and ionisation potential were calculated. Higher value of E H O M O and lower value of Δ E indicate the better inhibition efficiency of the compounds. Lower ionisation potential of inhibitors indicates higher reactivity and lower chemical stability.